Effects of CO2 concentration on acclimatization and physiological responses of two cultivars of carob tree - Osório, Maria Leonor (2013)
This study reports survival and physiological responses of micropropagated Ceratonia siliqua L. cvs. Galhosa and Mulata plants during ex vitro acclimatization under ambient (AC; 330 μmol mol-1) or elevated (EC; 810 μmol mol-1) CO2 concentration and a photosynthetic photon flux density of 125 μmol m-2 s-1. CO2 enrichment during acclimatization did not improve survival rate that was around 80 % for both treatments. Eight weeks after ex vitro transplantation, photosynthetic capacity and apparent quantum yield in acclimatized leaves were higher in comparison with those in in vitro-grown leaves, without any significant difference between CO2 treatments. Chlorophyll content increased after acclimatization. However, EC led to a decrease in the total amount of chlorophyll in new leaves of both cultivars, compared to those grown at AC. Soluble sugars and starch contents were not markedly affected by growth EC, although starch had significantly increased after transfer to ex vitro conditions. EC induced an increase in the stem elongation and in the effective life of leaves, and a decrease in the number of new leaves.